Influence of The Receivables Turnover Ratio and The Receivables Collection Period Ratio on Profitability with The Level of Non-Performing Financing as a Moderator at PT Adira Dinamika Multi Finance Tbk - Prayogo Aldino Crismanov Nainggolan; Rahima Br Purba; Agus Tripriyono (Cita konsultindo, 2025)
This study aims to analyze the effect of the receivable turnover ratio (RTO) and the ratio of the average collection period (ACP) to profitability (retun on assets/ROA) with the level of non-performing financing (NPF) as a moderation variable. The data in this study is in the form of secondary data, namely the quarterly financial statements of PT Adira Dinamika Multi Finance Tbk for the 2019-2023 period obtained from the company's official website. The data analysis techniques carried out were in the form of descriptive statistical analysis, classical assumption tests which included normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests (durbin-watson), multiple linear regression analysis, moderated regression analysis (MRA) analysis, hypothesis tests and determancy coefficients. The results of the study show that the receivables turnover ratio has a significant effect on profitability at PT Adira Dinamika Multi Finance Tbk. The ratio of the receivables collection period does not have a significant effect on profitability at PT Adira Dinamika Multi Finance Tbk. The non-performing financing rate is not able to moderate the effect of the receivables turnover ratio and the ratio of the receivables collection period to profitability at PT Adira Dinamika Multi Finance Tbk.